Education of Children Gifted in Music: Experience of Teachers of Vilnius Choir Singing School “Liepaitės” - Šečkuvienė, Henrika (Pedagogika, 2014)
Objective of this survey is to detect experience of teachers working with children gifted in music. 8 teachers from Vilnius choir singing school “Liepaitės” have participated in this survey. Teachers representing different education stages and subjects were selected to identify overall picture of experience in education of children gifted in music. Semi-structured interview was employed to reveal in-depth experience from teacher‘s position, understand his position, feelings, how he works with children gifted in music. Thematic analysis method was employed for data analysis. Thee most significant themes were emphasized in interview data analysis: identification of children gifted in music, meeting demands for musical expression of children with different musical abilities and professional self-perception of the music teachers. Analysis of Lithuanian education instruments disclosed that children gifted in music have special needs and adequate education is necessary to meet them. Children gifted in music are educated in music schools. Music education in these schools is increasingly oriented towards meeting demands of the students for musical expression, purposeful extracurricular activities of students. Students with very different level of musical abilities are educated in music schools. One of the most critical challenges in this context is the issue of organizing education, identifying those who are mostly gifted in music and facilitating successful development of their musical abilities and on the other hand ensuring high quality music education for children with lower musical abilities. Results of the survey indicate that in identifying children gifted in music and establishing level of their musical abilities teachers build on their experience and assume the role of an expert, however they consider this a very complicated matter. Analysis of teachers’ experience indicate that collective musical activity (choir) is a very efficient tool to meet demands for musical expression of students with different musical abilities. Most students feel urged for achieving high learning results. Concert activities, continuous school traditions, consistency of education, continuity and succession, individual approach towards every student are elements which contribute most to the students’ motivation for learning. Results of the survey revealed that teachers feel satisfaction with their profession, employment position and it contributes to the possibility of being a member of powerful school community and team of professional teachers. Teachers analyse, perceive arising problems. They are concerned about the fact that some parents of the students regard musical education of the children as entertainment and not a systematic, responsible learning. Outdated programs, repertoire are indicated as a weakness. Teachers reflect on their activity and feel the demand for adaptation and changes in the context of dynamics of modern education.